Relation between systemic hypertension and sleep hypoxaemia or snoring: analysis in 748 men drawn from general practice. - Stradling, JR; Crosby, J (1990)
OBJECTIVE: To establish whether a history of snoring or the degree of overnight hypoxaemia is an important independent predictor of systemic blood pressure. DESIGN: Prospective community based study of blood pressure in relation to overnight oxygen saturation, height, weight, and a questionnaire assessment of snoring, smoking, and alcohol consumption. Analysis was by multiple linear regression techniques and analysis of variance. SETTING: Small town outside Oxford, served by one group general practice of four partners. All measurements were made at home. SUBJECTS: The names of 836 men aged 35-65 were drawn at random from the general practitioners' age and sex register and the men then asked to participate; 752 (90%) agreed. MAIN OUTCOME MEASURES: Systolic, mean, and diastolic blood pressures and their association with age, obesity, alcohol consumption, cigarette consumption, snoring, and overnight hypoxaemia. RESULTS: Though systemic blood pressure correlated significantly with overnight hypoxaemia, this was due to the cross correlation with age, obesity, and alcohol consumption. No independent predictive effect of overnight hypoxaemia was found. Snoring was correlated with systemic blood pressure but not significantly so and also was not an independent predictor once age, obesity, and alcohol consumption had been allowed for. CONCLUSIONS: It is unlikely that snoring and sleep hypoxaemia from occult sleep apnoea are important causes of diurnal systemic hypertension when compared with age, obesity, and alcohol consumption. The increased prevalence of cardiovascular complications reported in snorers may be due to the confounding variable of obesity or to nocturnal rises in blood pressure that are not reflected in the daytime figures.